THE CONCEPT OF "HUMA BETANG" AS A MODEL OF THE VALUES OF THE PHILOSOPHY OF LIFE OF THE DAYAK COMMUNITY IN CENTRAL KALIMANTAN - Loi, Anjelinus; Kwirinus, Dismas; Peri, Heribertus (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
The focus of this article is to review the philosophical meaning of the Central Kalimantan traditional house called Huma Betang, in relation to the philosophical values of life of the people of Central Kalimantan. Huma Betang Dayak of Central Kalimantan is a cultural product in which there is a system of human values or life norms based on kinship, togetherness and equality. Huma Betang also presented the collectivity principle of living together, side by side with others. This research will explain that the first objective is to find the philosophical values that the Dayak people have actually lived out which are reflected in the daily dynamics of Huma Betang. This study uses phenomenological analysis and critical reading of the text, using qualitative research methods. The research findings show that the Dayak people of Central Kalimantan in their daily lives in Huma Betang are still very strong in maintaining philosophical values, especially hafakat basara and handep.